2014
DOI: 10.3389/fpsyg.2014.00166
|View full text |Cite
|
Sign up to set email alerts
|

The influence of banner advertisements on attention and memory: human faces with averted gaze can enhance advertising effectiveness

Abstract: Research suggests that banner advertisements used in online marketing are often overlooked, especially when positioned horizontally on webpages. Such inattention invariably gives rise to an inability to remember advertising brands and messages, undermining the effectiveness of this marketing method. Recent interest has focused on whether human faces within banner advertisements can increase attention to the information they contain, since the gaze cues conveyed by faces can influence where observers look. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 53 publications
(93 reference statements)
6
56
1
Order By: Relevance
“…This is in line with previous research that suggested that the observation of gaze cuing leads to an attentional shift toward the looked-at region (Hutton and Nolte, 2011; Sajjacholapunt and Ball, 2014; Droulers and Adil, 2015). Increasing the likelihood that a product will be noticed already constitutes an important first step for advertisements to arouse a consumer’s interest.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in line with previous research that suggested that the observation of gaze cuing leads to an attentional shift toward the looked-at region (Hutton and Nolte, 2011; Sajjacholapunt and Ball, 2014; Droulers and Adil, 2015). Increasing the likelihood that a product will be noticed already constitutes an important first step for advertisements to arouse a consumer’s interest.…”
Section: Discussionsupporting
confidence: 93%
“…There are a few factors that may explain this deviation from Sajjacholapunt and Ball’s (2014) original findings. First, the banner advertisement that we used was smaller in size than the advertisements that were used originally.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Against this backdrop, web advertising has gained a great deal of attention in recent years due to its potential effect on online shoppers' responses (Almendros & García, 2014;Ching, Tong, Chen, & Chen, 2013;Flores, Chen, & Ross, 2014;Goodrich, 2011;Kuisma, Simola, Uusitalo, & Öörni, 2010;Saadeghvaziri, Dehdashti, & Askarabad, 2013;Sajjacholapunt & Ball, 2014;Sokolik, Magee, & Ivory, 2014). While previous studies have identified the impacts of web advertising on basic consumer reactions such as click-through rates and consumer recall, a significant gap remains in the theoretical understanding of how WAVD influences online purchase intention (Cyr, Head, Larios, & Pan, 2009;Goodrich, 2011).…”
mentioning
confidence: 99%
“…For all other uses, contact the owner/author(s). MM'17, October [23][24][25][26][27]2017, Mountain View, CA, USA. © 2017 Copyright held by the owner/author(s).…”
Section: Introductionmentioning
confidence: 99%